First Global Report on Mud-puddling by Pyraloidea from India (Insecta: Lepidoptera) - Avishek Talukdar; Soumyajit Chowdhury (SHILAP)
Mud-puddling though very common phenomenon in case of Rhopalocera (especially males) is not so common for Heterocera. The phenomenon was observed during one trapping night at Tippi village in Arunachal Pradesh, India. Here the authors present the first global report of Pyraloidea from India